Fungal isolation from wound samples submitted for culture at a tertiary care hospital laboratory - Farooqi, Joveria; Akbar Ladak, Asma; Shaheen, Najma; Jabeen, Kauser (Journal of the Pakistan Medical Association, 2022)
Fungal wound infections are increasing worldwide. The aim of this retrospective study, conducted at the Aga Khan University laboratory, Karachi, Pakistan, was to determine the frequency of fungal isolation in wound specimens. Data of wound samples received for culture from all over the country between September and October 2018 was reviewed. Samples were processed for bacterial cultures and additionally inoculated on Sabouraud’s dextrose medium. Demographic information, medical history and information on the type of wound was collected. A total of 140 cases were included, of which 87 (81%) were culture positive, while 10 (7%) cases yielded fungi. Burn and blast wounds had the highest proportion of fungal isolation, i.e. 2 out of 4 (50%). Candida species were the most common fungi (n=4), followed by Fusarium species (n=3). This study reports an alarming rate of fungal wound infections. As fungal necrotising wound infections have high morbidity and mortality, it is, therefore, important to accurately diagnose and treat such infections in local setting. Keywords: Wounds and Injuries, Fungal Infections, Diabetic Foot, Infections, Skin and Soft Tissue Infections.